Información para los propietarios: Cancro Cítrico - Megan M. Dewdney; Mongi Zekri; Pamela D. Roberts; Jamie D. Burrow (EDIS)
This 4-page fact sheet is the Spanish-language version of PP194/PP116: Homeowner Fact Sheet: Citrus Canker. It is a minor revision written by M. M. Dewdney, Mongi Zekri, P. D. Roberts, and Jamie D. Burrow, and published by the Plant Pathology Department, February 2019.